Does Reinfusion of Stem Cell Products on Multiple Days Affect Engraftment? - Medeni, Serife Solmaz; Turkyilmaz, Dogus; Acar, Celal; Sevindik, Omur Gokmen; Yuksel, Faize; Piskin, Ozden; Ozsan, Guner Hayri (Galenos Yayincilik, 2018)
Objective: High-doses of melphalan treatment with autologous stem cell transplantation in multiple myeloma (MM) remains a major treatment modality in suitable patients. A minimal dose of 2x10(6)/kg CD34+ cells is preferred to achieve engraftment. Some patients need multiple leukapheresis procedures to achieve the necessary number of CD34+ cells, but this can cause a high volume of stem cell product that cannot be given in a single day. Whether or not the number of infusion days affects engraftment has not been studied before. We aimed to evaluate the impact of reinfusion of stem cells on multiple days on engraftment results. Materials and Methods: Demographic features, CD34+ cell doses, neutrophil and platelet engraftment days, hospitalization days, and number of infusion days of 149 autologous transplantations of 143 MM patients were evaluated retrospectively. Results: The data of 143 MM patients who were transplanted were analyzed retrospectively. Median age was 55 +/- 8.5 (range: 26-70) years with a male/female ratio of 91/58. Hospitalization days for all patients were 24 +/- 6 (range: 14-50) days. Mean CD34+ cell number was (7.5 +/- 5.3) x10(6)/kg (range: 1.5-31x10(6)/kg). CD34+ cells were reinfused in 1 day in 80.5% (n=120) of the patients, 2 days in 18.2% of the patients (n=27), and 3 days in 1.3% of the patients (n=2). For 29 patients, reinfusion was applied in more than 1 day because of the high volume of stem cell product. We did not see any dimethyl sulfoxide toxicity, cardiac arrhythmia, or volume overload complications. Hypertensive attacks during infusion were easily controlled by furosemide treatment. In the group with multiple infusions, the infused CD34+ cell numbers had a mean of (4.8 +/- 2.8)x10(6)/kg, and in the single infusion group the mean was (8.1+5.5)x10(6)/kg. There were no statistical differences between the two groups regarding platelet and neutrophil engraftment days (p=0.850, r=0.820 and p=0.500, r=0.440). There was no statistical difference between the two groups for hospitalization days (p=0.060, r=0.050). Conclusion: In cases with a high volume of stem cell product to acquire adequate stem cells, reinfusion can be safely applied across multiple days without any delay in engraftment.
Çoklu gün kök hücre reinfüzyonu engrafmanı etkiler mi?
Keywords: Multiple myeloma; Autologous transplantation; Multiple reinfusion days